Endocrine malignancies: a still neglected issue in kidney transplantation - Bianca Pellegrini; Francesca Leone; Rosita Greco; Marcello Maggiolini; Michele Provenzano; Michele Provenzano; Gianluigi Zaza; Gianluigi Zaza (Frontiers in Medicine)
Advances in kidney transplantation have made significant progress, yet challenges remain in managing both the pre- and post-transplantation phases, which have a direct impact on long-term allograft survival and comorbidities experienced by kidney transplant recipients (KTRs). Among the common immunosuppression-related complications, malignancies are a notable concern, and endocrine tumors are frequently observed. These tumors exhibit heterogeneous pathogenesis, prognosis, and treatment responses but existing literature is limited, and prevalence studies often compare KTRs to the general population. Thyroid cancers (particularly papillary thyroid cancer) have a high incidence in KTRs, whereas rare endocrine malignancies (such as neuroendocrine tumors, adrenal cortical carcinomas, pheochromocytomas, paragangliomas, and parathyroid carcinoma) are mostly reported in isolated case reports, and no clinical trials have been performed to assess the impact of different immunosuppressive treatments on their onset and development. However, current guidelines for the management of post-transplant malignancies suggest reducing or withdrawing immunosuppressive therapy whereas a switch from calcineurin inhibitors to mammalian target of rapamycin (mTOR) inhibitors is currently not recommended due to limited supporting data. Notably, the pathogenic role of transplantation and the timeline for endocrine malignancies onset in KTRs are poorly defined. To address these challenges, a multicenter and interdisciplinary approach is critical to improve our understanding of the epidemiology and pathogenesis of endocrine malignancies in KTRs. Additionally, specific guidelines for early diagnosis and treatment are necessary to ensure safe and effective management of these tumors in this vulnerable population. This mini-review aims to synthesize the available data and current insights into this important issue.